Marketing in the Transformation Economy - Pranulis, Vytautas (Ekonomika, 2000)
The role, nature, and ideology of marketing across transitional type of economy is examined in this article. The objective and subjective rudiments of marketing arc discussed in this paper. Of interest here is whether Lithuanian Universities need to adopt marketing studies programmes in order to accelerate process creation of contepporary market environment. This paper offers an exploratory study adaptation of marketing subjects in the curricula’s of business studies in there universities of Lithuania. Specific interest is given to the problems organisation of marketing studies at Vilnius University. The patterns of problem solving are suggested.